Asian crisis : balance sheet restructuring : a look at corporate restructuring and deleveraging in various industries - M. Nazirin (2008)
The Asian financial crisis of 1997-1998 had a severe negative impact on Asian economies. We analyze various financial performance indicators of companies/industries in Korea, Malaysia, Thailand, Indonesia and Singapore to assess corporate restructuring and deleveraging. Industries are airlines, construction, electronics, food, hotels, industrial commercial machinery, real estate and telecommunications.